New zooarchaeological evidence from Pictish sites in Scotland: implications for early medieval economies and animal-human relationships - Masson-MacLean, Edouard; Niehaus, Sesilia; Fraser, Elizabeth; Lee, Veronica; Prado, Shalen; Czére, Orsolya; Fawcett, Jovita; O'Driscoll, James; Girdland-Flink, Linus; Noble, Gordon; Britton, Kate (Frontiers in Environmental Archaeology, 2023)
Our knowledge of the use of livestock in early medieval Scotland is fragmentary and relies on a handful of well-studied faunal assemblages, with few from Pictland (north-east Scotland), an important and enigmatic group and latterly kingdom in Northern Britain that existed between the 3rd and 9th centuries AD. The assemblages that have been recovered and studied mainly occur at the limits of this territory, beyond the heartland of the Picts in the northern and eastern mainland. Recent archaeological excavations at three high-status sites in eastern Scotland have unexpectedly yielded well-preserved faunal remains providing a unique and long-awaited opportunity to explore further human-animal relationships and the use of animals in Pictish society. This paper presents new data from the initial study of these assemblages. It discusses the implications in terms of animal economy in Pictland, the potential of these sites to yield larger faunal assemblages and the directions of future research. Results show that cattle were a pivotal element of the economy, playing a multi-faceted role (beef and secondary products), pigs ranked second in frequency which likely reflects the high status of these sites and sheep appear as a marginal resource and were primarily raised for consumption. Results also suggest that these sites may have operated within an integrated network rather than functioning solely as self-sufficient entities.